Potential of the Rainwater Harvesting Method in Fulfilling Domestic Water Needs at SD Negeri 02 Gunung Terang Bandar Lampung - Putra, Muhammad Hakiem Sedo (Jurnal Teknik Sipil, 2023)
The city of Bandar Lampung has progressed quite rapidly in infrastructure development sector. Schools are one of the public infrastructure facilities that have experienced significant development, which is in line with the increasing number of school students in the city of Bandar Lampung. The increase in number of students is certainly linear with the basic needs of the school, both for existing facilities and infrastructure. One of the basic needs of schools is the need for water. In water supply, there are several alternative methods that can be used by the community, one of which is Rainwater Harvesting (RWH) or commonly known as Pemanenan Air Hujan (PAH) in Bahasa Indonesia. This study is intended to determine the potential of RWH when implemented in elementary schools. The first thing to do is to find out the secondary data in the form of the number of people in the school, the roof area, and the rainfall that occurs in the school. Then after obtaining secondary data, a simulation of the RWH is carried out, whether it can meet the domestic water needs of all people in the school. The general public is expected the benefit from this research as a reference, and the main thing is to become a reference for schools for Rainwater Harvesting (RWH) installations.